Pulsed radiofrequency treatment of articular branches of femoral and obturator nerves for chronic hip pain - Chye CL; Liang CL; Lu K; Chen YW; Liliang PC (Clinical Interventions in Aging, 2015)
Cien-Leong Chye,1 Cheng-Loong Liang,1 Kang Lu,1 Ya-Wen Chen,2,3 Po-Chou Liliang1 1Department of Neurosurgery, E-Da Hospital, I-Shou University, 2Department of Nursing, I-Shou University, 3School of Nursing, Kaohsiung Medical University, Kaohsiung, Taiwan Purpose: Chronic hip pain is a common symptom experienced by many people. Often, surgery is not an option for patients with multiple comorbidities, and conventional drugs either have many side effects or are ineffective. Pulsed radiofrequency (PRF) is a new method in the treatment of pain. We attempt to compare the efficacy of PRF relative to conservative management for chronic hip pain.Patients and methods: Between August 2011 and July 2013, 29 patients with chronic hip pain were divided into two groups (PRF and conservative treatment) according to consent or refusal to undergo PRF procedure. Fifteen patients received PRF of the articular branches of the femoral and obturator nerves, and 14 patients received conservative treatment. Visual analog scale (VAS), Oxford hip scores (OHS), and pain medications were used for outcome measurement before treatment and at 1 week, 4 weeks, and 12 weeks after treatment.Results: At 1 week, 4 weeks, and 12 weeks after treatment initiation, improvements in VAS were significantly greater with PRF. Improvements in OHS were significantly greater in the PRF group at 1 week, 4 weeks, and 12 weeks. Patients in the PRF group also used less pain medications. Eight subjects in the conservative treatment group switched to the PRF group after 12 weeks, and six of them had >50% improvement.Conclusion: When compared with conservative treatment, PRF of the articular branches of the femoral and obturator nerves offers greater pain relief for chronic hip pain and can augment physical functioning. Keywords: pulsed radiofrequency, obturator and femoral nerves, hip joint pain, osteoarthritis